2009
DOI: 10.1179/136404609x368109
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the metal/die interfacial heat transfer coefficient and its application in evaluating the pressure distribution inside the casting during the high pressure die casting process

Abstract: High pressure die casting (HPDC) experiments were conducted on a 650 t cold chamber die casting machine to study the interfacial heat transfer behaviour between casting and die. A 'step shape' casting and two commercial alloys namely ADC12 and AM50 were used during the experiments. Temperature and pressure measurements were made inside the die and at the die surface. The metal/die interfacial heat transfer coefficient (IHTC) was successfully determined based on the measured temperature inside the die by solvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
2
Order By: Relevance
“…Some studies have shown that the applied pressure will affect the interface heat transfer coefficient between the metal melt and the metal die [ 47 , 48 , 49 , 50 , 51 ]. It is generally believed that the liquid contacts the metal surface more closely after the melt is pressurized.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that the applied pressure will affect the interface heat transfer coefficient between the metal melt and the metal die [ 47 , 48 , 49 , 50 , 51 ]. It is generally believed that the liquid contacts the metal surface more closely after the melt is pressurized.…”
Section: Methodsmentioning
confidence: 99%
“…Determining the heat flux from the alloy to the sand often involves experimental measurements or numerical simulations [11], as it depends on various factors such as contact pressure, surface finishing, sand grain dimensions, coating thickness, and deformation of the casting, which can be difficult to model analytically. In GSC simulations, this heat flux is modelled as an overall Heat Transfer Coefficient (HTC), which is the proportionality constant between heat flux and temperature difference between the contacting surfaces per unit area [12,13]. The HTC between casting and mould surfaces is not precisely known, and the simulations rely on typical HTC values available in the software database.…”
Section: Introductionmentioning
confidence: 99%
“…8 Inverse problems in heat transfer involve thermal parameter and boundary condition estimation using the measured thermal history, noting that when thermal properties are a function of temperature, the problem becomes non-linear. 9 Various numerical techniques involving heuristics, gradient-based or other classical optimisation methods have been employed for the solution of inverse problems in casting, e.g. 'control volume technique', 10 'Maximum a Posteriori (MAP)' algorithm, 11 etc.…”
Section: Introductionmentioning
confidence: 99%